A1_5 Nightclub energy - Weightman, Louise; Farr, Sam; Syed, Muhammad Zaryab; Dakin, Henry (Physics Special Topics, 2021)
In this paper we have examined how much heat all the students who attend the weekly student night would generate. We have calculated the maximum energy generated to be 4.19 x 109 Joules. The various ways that this energy could be converted into something more useful have been considered. The assumed usable energy is 1.257 x 109J which would be sufficient to power the electrical systems at ’Let’s Disko’ with the excess contributing to the reduction of heating costs.